BALANCED SCORECARD ANALYSIS TO DETERMINE COMPANY STRATEGY IN THE FUTURE AT SELECTA RECREATION PARK - Tiffany, Denissa Nadya; Subekti, Imam (Jurnal Ilmiah Mahasiswa FEB, 2013)
The research was conducted in Selecta Recreation Park since the increase of competition in the tourism industry in Kota Batu. As the oldest tourist which features nature, Selecta Recreation Park has to have a strategy in order to be able to compete with other tourism entrepreneurs. To realize this strategy, the company should have a good performance measurement system. The purpose of this study is to analyze the performance of Selecta Recreation Park by using the Balanced Scorecard method. The use of the Balanced Scorecard is to measure the performance of companies through the four perspectives which are: financial perspective, customer perspective, internal business processes perspective, and learning and growth perspectives. From the results of measurements that have been achieved, it can be seen that overall the performance of the Selecta Recreation Park has been good. It can be seen from scorecard tables that exist in every perspective. In the financial perspective suggests that performance on this perspective is good. In the customer perspective, the scorecard table shows that the performance is already good. In the internal business process perspective, it can be concluded that this perspective is considered very good. In the learning and growth perspective, researcher concludes that the performance is also good. The conclusion that can be drawn from the results of the analysis that was done, is that the Balanced Scorecard is a performance measurement tool that is suitable to be applied in Selecta Recreation Park. This is because the Balanced Scorecard is able to measure non-financial performance such as customer perspective, internal business processes perspective and learning and growth perspective. Keywords : performance measurement, BalancedÂ  Scorecard